Research in the sociology of work. Vol. 29 - Vallas, Steven P. 1951- (Emerald, 2016)
Research in the Sociology of Work (RSW) is a twice yearly publication that examines current issues related to the sociology of work. The series provides a comprehensive collection of research focused on the social, economic, political and cultural aspects of work and labour. This volume includes contributions which discuss: work and identity, including the experiences of actors and teachers; authority and control at work, including insights from the hospitality and publishing industries; and issues of gender and sexuality in the workplace, including insights on sexual harassment in the workplace.
Keywords: Business & Economics -- Labor.; Sociology: work & labour.; Industrial sociology.; elektronické knihy; electronic books